Formulation Optimization and In Vitro Antioxidant Evaluation of a Polyherbal Nanosuspension Incorporating Apium graveolens, Centella asiatica, and Orthosiphon stamineus - Astuti, Febriana; Akrom; Mustofa; Setianto, Arif Budi; Hidayati, Titiek (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Antioxidants play a crucial role in protecting cells from damage caused by free radicals, particularly reactive oxygen species (ROS). Herbal plants contain various bioactive compounds, such as phenolics, flavonoids, terpenoids, and alkaloids, which exhibit strong antioxidant properties to neutralize these harmful molecules. However, the bioavailability of these compounds is often limited due to their poor water solubility. Nanotechnology offers a promising solution, specifically through the development of nanosuspensions. This approach enhances the solubility of these compounds by reducing their particle size to the nanometer scale, thus improving absorption in the body. In this study, nanosuspensions were formulated using extracts from Apium graveolens, Centella asiatica, and Orthosiphon stamineus through a two-factor optimization approach with Design-Expert® version 13 software. The optimal formulation contained 25 mL of chitosan, 6 g of Tween 80, and 10 mL of sodium tripolyphosphate (Na-TPP), resulting in nanosuspensions with an average particle size of 220.00(1157) nm, a polydispersity index (PDI) of 0.59±0.06, and a zeta potential of −28.27±0.37mV. The antioxidant activity was evaluated using DPPH and ABTS assays. In the DPPH assay, the nanopolyherbal formulation showed an IC50 of 41.780(3064) μgmL−1, while the combined extract had an IC50 of 44.930(2989) μgmL−1. The ABTS assay revealed an IC50 of 28.21 μgmL−1 for the nanosuspension, significantly lower than the combined extract’s 54.22 μgmL−1. These results highlight the superior antioxidant activity of the nanosuspension, emphasizing the potential of nanotechnology to enhance the efficacy of bioactive compounds from herbal plants.